Peripherally inserted central catheter at the Neonatal Intensive Care Unit - Cabral, Patrícia Fernanda de Almeida (2013)
ABSTRACT The objective of this study was to outline the profile of the newborns who used PICC. This retrospective, descriptive study was performed with a sample of 163 newborns. The data were collected from the records of newborn inpatients at a Neonatal Intensive Care Unit (NICU) of a University Hospital in Florianópolis, Santa Catarina, Brazil, between the years of 2004 and 2009. Most newborns were male, of white ethnicity and medically diagnosed with prematurity. Most punctures were performed on the upper limbs and were due to the need for parenteral nutrition. Most catheters were removed only at the end of treatment, and the tips were sent for culture. PICC avoided repeated punctures, as most newborns showed venous frailty due to their prematurity. The pathogen found in the culture, Staphylococcus sp., is part of the skin microbiota, which suggests a need for greater precaution in the placement and maintenance of the PICC. Descriptors: Infant, Newborn; Intensive Care Units, Neonatal; Neonatal Nursing; Catheter-Related Infections.